Assessment of Selected Environmental Soil Contaminants in Relation to Industrial and Urban Activities in South-West Nigeria - Agbeyangi, Christianah Oluwaseun; Bello, Tesleem; Sojinu, O. S. (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
Rapid industrialization and urbanization in South-West Nigeria have intensified environmental pressures, leading to significant soil contamination. This study assessed the concentrations and associated risks of selected heavy metals (Pb, Cd, Cr) and plastic-derived organic pollutants (Polybrominated Diphenyl Ethers, PBDEs; Phthalate Esters, PAEs) in soils from four major landfill sites in Lagos and Ogun States. Results revealed significant heavy metal contamination, particularly at the Olusosun landfill, which exhibited the highest Cadmium (Cd) concentration (3.63 ± 0.45 mg/kg). Phthalate Esters (PAEs) were prevalent across all sites, with Di(2-ethylhexyl) phthalate (DEHP) being the most abundant congener, reaching a maximum concentration of 17.7 ± 2.1 mg/kg at Olusosun. Ikorodu also showed high levels of DEHP (11.3 ± 1.5 mg/kg) and Dicyclohexyl phthalate (DCHP) (11.28 ± 1.4 mg/kg). In contrast, concentrations of the analyzed PBDEs were generally low, with the highest level detected for BDE-153 at Olusosun (0.020 mg/kg). Ecological risk assessment indicated a "considerable potential ecological risk" (Individual Risk Factor, E_r = 110.18) from Cd at the Olusosun site, primarily linked to e-waste and battery disposal. Furthermore, the Hazard Index (HI) for phthalates exceeded the safe threshold (HI > 1) at all sites, with particularly high values at Ikorodu and Sango, indicating a significant non-carcinogenic health risk to exposed populations. These findings highlight Olusosun as a hotspot for Cd pollution and reveal widespread health risks from PAEs, underscoring the urgent need for improved waste segregation, engineered landfill management, and robust environmental monitoring to mitigate pollution and protect public health in the region. Keywords:  Soil Contamination, Polybrominated Diphenyl Ethers (PBDEs), Phthalate Esters (PAEs), Heavy Metals, Industrial Pollution, Urbanization, E-waste, South-West Nigeria.